A numerical analysis of airflows caused by train-motion and performance evaluation of a subway ventilation system. Issue 6 (October 2014) - Yan, Wu; Naiping, Gao; Lihui, Wang; Xiping, Wu
A numerical analysis of airflows caused by train-motion in one-shaft subway system and two-shaft subway system was carried out using computational fluid dynamics (CFD) method. The dynamic mesh method was used to model the moving boundaries of the train. The geometry model and train-operation schedule employed were exactly the same as the real situation. The CFD model was validated against field measurement data. The performance of natural ventilation system impacted by the location and number of the vent shafts was evaluated by two indexes, i.e. net exhaust air volume, Ne, and net suction air volume, Ns . The result shows that a subway system with two shafts rather than that with one shaft could dramatically improve performance in air exchange efficiency. For the one-shaft system, it performed better when the shaft was located at the train-arrival side rather than at train-departure side.